2009
DOI: 10.1038/bmt.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of HHV-6 viral load and plasma IL-6 concentration with HHV-6 encephalitis in allogeneic stem cell transplant recipients

Abstract: This study investigated factors associated with the development of human herpesvirus (HHV)-6 encephalitis. Among 111 enrolled subjects, 12 patients developed central nervous system (CNS) dysfunction. CNS dysfunction in four patients was found to have no association with HHV-6. The remaining eight patients displayed HHV-6 encephalitis (n ¼ 3), limbic encephalitis (HHV-6 DNA in cerebrospinal fluid was not examined; n ¼ 3) or CNS dysfunction because of an unidentified cause (n ¼ 2). Realtime PCR showed CNS dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
3
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 33 publications
3
84
3
3
Order By: Relevance
“…10,45,46 However, several lines of evidence suggest that other cellular factors in addition to CD46 are crucial to the establishment of active HHV-6 infection in vivo. 41 Ogata et al 47 demonstrated that serum IL-6 levels increase dramatically in patients experiencing HHV-6 reactivation, showing a correlation between high levels of IL-6 in serum and CSF and the development of encephalitis. Several other studies have also suggested a significant role for IL-6 in the development of encephalitis through various proposed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,45,46 However, several lines of evidence suggest that other cellular factors in addition to CD46 are crucial to the establishment of active HHV-6 infection in vivo. 41 Ogata et al 47 demonstrated that serum IL-6 levels increase dramatically in patients experiencing HHV-6 reactivation, showing a correlation between high levels of IL-6 in serum and CSF and the development of encephalitis. Several other studies have also suggested a significant role for IL-6 in the development of encephalitis through various proposed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, this prevalence level is most likely an underestimate because some patients develop encephalitis/myelitis with positive imaging findings in the limbic area and high levels of DNA in the plasma, but are unable to undergo lumbar puncture for various clinical reasons, including severe thrombocytopenia or deteriorated general condition. 11 Ogata et al 47 reported that, in cases where lumbar puncture is not possible, CNS dysfunction concomitant with high-level HHV-6 DNA detected in plasma via real-time PCR may be used to diagnose HHV-6 encephalitis in the absence of CSF testing. This group also found that encephalitis was only associated with plasma DNA loads of 410 4 , although CNS dysfunction was associated with low levels of plasma HHV-6 DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The duration of displaying positive HHV-6 DNA in plasma is only 1-2 weeks in most cases. 3,5,7,8 HHV-6B accounts for most reactivation events. 1,12 Risk factors for displaying HHV-6 reactivation are HLA mismatch, 3,4 steroid treatment, 1,3 transplants from unrelated donors 2,3 and umbilical cord blood transplantation (UCBT).…”
Section: Hhv-6 Reactivation and Hhv-6 Encephalitis: We Know Hhv-6 Reamentioning
confidence: 99%
“…1,[3][4][5][6][7][8] The first case of HHV-6 encephalitis after allo-HCT was described in 1994 by Drobyski et al 9 Since then, a significant amount of information regarding the incidence, risk factors, therapy and outcomes has been reported. Over the past decade, HHV-6 encephalitis has become well known as a significant complication of allo-HCT.…”
Section: Introductionmentioning
confidence: 99%